Comercio electrónico global y colaboración e innovación en Procter & Gamble - Lasluisa Morales, Richard Guillermo (2018)
This article is an academic research related to electronic commerce work, collaboration tools andinnovation applied in the company Procter & Gamble, which is one of the most successful companiesworldwide in the development of new brands beauty care products, home care, health and beauty.Describe your business model, collaboration tools have implemented and open innovation has helpedto achieve the goals of this organization. Describes a proposal to implement other ways to implementcollaborative work and a methodological process for the selection of collaborative tools applied to smalland medium enterprises; finally it has a study of the Ecuadorian reality environment the application ofgovernment, commerce and innovation.